Utilization Of Edible Film from Taro Starch And Chicken Feet Gelatin As Packaging For Instant Noodles Seasoning - Risti, Mella; Leffy Hermalena; Fitria, Eddwina Aidila; Yessirita, Nita (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This research aims to investigate the ability of packaging edible film made from taro starch and claw gelatin chicken in dry instant noodles, and to determine the effect of storing packaged noodle seasoning with edible films made from taro starch and claw gelatin chicken. This research employed a Completely Randomized Design (CRD) with five levels and three replications. The results of the observational data were analyzed using ANOVA, and the DMRT was further tested at a significance level of 1%. Treatment in research involves storing noodle seasoning with packaging that is edible for 1, 4, 7, 10, and 13 days. Research results show that packaging season noodles with edible film during storage very real effect on water content, solubility, humidity, and total plate count (TPC). Edible film of taro starch and claw gelatin chicken is effective for packaging dry noodles in a temperature-controlled space for 1 to 4 days, with a water content of 20.96%, solubility of 15.74 minutes, humidity of 0.02g, and a total plate count (TPC) of 1.08 x 10^4 colonies/g. Noodle seasoning packaged with edible film has a detrimental effect on storage at room temperature, causing damage. Season noodles with edible packaging film after long storage for 7 days (treatment), especially focusing on water content and total plate count (TPC), with a water content of 23.06% and a total plate count (TPC) of 5.8 x 10^4 colonies/g. Contribution to Sustainable Development Goals (SDGs):SDG 2 – Zero HungerSDG 9 – Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production